Angiotensin-converting Enzyme Inhibitor Angioedema Requiring Admission to an Intensive Care Unit - Soo Hoo, Guy W.; Lin, Henry K.; Junaid, Imran; Klaustermeyer, William B. (The American journal of medicine, 2015)
The purpose of this study was to review consecutive cases of angiotensin-converting enzyme (ACE) inhibitor angioedema admitted to an intensive care unit. Fifty subjects with ACE-inhibitor angioedema admitted from 1998-2011 were reviewed. All 50 subjects were men, 62.8 ± 8.4 years of age, 76% African Americans. Fifteen (30%) required ventilatory support and 2 (4%) required tracheostomy. Over half (56%) had taken ACE inhibitors for over a year. Logistic regression identified dyspnea and tongue involvement with the need for ventilatory support (P < .01). Hypercapnia (PaCO2 = 45.2 ± 6.7; P = 0.046) also identified patients needing ventilatory support. Ventilatory support was provided for about one-third of those with ACE inhibitor-associated angioedema. Angioedema can occur even after extended use. Dyspnea and tongue involvement identified patients requiring ventilatory support.